Deterioration of Physical and Mechanical Properties of Rocks by Cyclic Drying and Wetting - Zhizhen Zhang; Yixin Niu; Xiaoji Shang; Peng Ye; Rui Zhou; Feng Gao (Geofluids)
Both surface and underground rocks in nature often undergo repeated drying and wetting. The dry-wet cycle is a weathering effect that includes physical and chemical processes, which has varying degrees of degradation effects on the physical and mechanical properties of rocks. This paper analyzes and discusses this kind of rock degradation based on the existing literature data. First, the deterioration degree of various physical and mechanical properties (including density, P-wave velocity, porosity, static and dynamic compressive/tensile strength, and fracture toughness) is summarized as the number of dry-wet cycles increases. Secondly, the possible degradation mechanism of the dry-wet cycle is explained in terms of clay mineral swelling, solute migration, and microcrack evolution. Then, the damage constitutive model of the rock after cyclic dry-wet treatment is introduced. Finally, the issues that need to be studied in the future are put forward.